PENGARUH PEMBELAJARAN DARING BERPRAKTIKUM MENGGUNAKAN MEDIA TRACKER BERBASIS INKUIRI TERBIMBING TERHADAP PENINGKATAN KEMAMPUAN INTERPRETASI GRAFIK - Ayu Nurjanah; I Dewa Putu Nyeneng; Ismu Wahyudi (JURNAL INOVASI DAN PEMBELAJARAN FISIKA, 2021)
This study aims to determine the effect of practicing online learning using tracker analysis media on the ability to interpret graphs. The sample of this research is the students of class X MIPA 3 SMA Negeri 1 Tanjung Bintang. The research design used is the One Group Pretest-Posttest Design. Online learning is carried out by conducting partly elastic collision-based practicum activities based on guided inquiry. The experimental data were processed using tracker analysis media. Data on students' graph interpretation abilities were obtained from the pretest and posttest scores. The analysis technique uses Paired Sample T-Test. Based on the results that practicing online learning using tracker analysis media can improve the ability to interpret graphs well with a significance value of 0.00. The results of the analysis of the average score of graph interpretation skills increased with the acquisition of an N-gain of 0.39 in the medium category.